Fabrication and characterization of photovoltaic cell with novel configuration ITO/n-CuIn3Se5/p-CIS/In. Issue 1 (17th February 2015) - Geethu, R; Jacob, R; Sreenivasan, P V; Shripathi, T; Okram, G S; Philip, R R
Abstract: A novel configuration ITO/n-OVC CuIn3 Se5 /p-CIS/In solar cell has been fabricated by multisource vacuum co-evaporation technique on soda lime glass substrates. The pn junction is formed with ordered vacancy compound as the n counter part for the p type CuInSe2 . The structural, compositional, hall coefficient, optical and electrical properties of the p and n layers have been studied respectively by X-ray diffraction, Energy Dispersive Analysis of X rays, optical absorbance and conductivity measurements. Current density-Voltage measurements enabled the determination of efficiency of the device.